Children 7-9 Years of Age Coping with a Parent Diagnosed with Cancer - Kulari, Genta (Mediterranean Journal of Social Sciences, 2012)
Statistically, one in three families has a member diagnosed with cancer at one point in life (Veach and Nicholas,1998), however other than the sick member of the family, it has been noticed that the rest of the family is emotionally touched bythis deviation from their regular lives. Couple relationships in these cases and especially the psychological state of the patienthave been crucial to researchers. Other members of the family, such as the children, are often disregarded and not dealt withthe same endeavor as the couple or the cancer patient. Young children for instance, often reveal signs of somatic andpsychological disorders associated with typical behaviors to attract attention. This psychological study focuses on the analysis ofthese typical behaviors that lead to the Inferiority Complex generated in children 7-9 years of age who have a parent diagnosedwith cancer. It identifies two conditions that bring to the development of this complex; these being the self-evaluation of the childin this period, and the interactions and relationships with peers in school. Another purpose is to identify and study compensativeperfectionist behaviors that these children activate by taking more responsibility upon them and exchanging roles in the family,from a parent-child to a child-parent environment and vice versa. Variables that can influence the behavioral changes includechild gender, sick parent, childâ€™s caretaker (nanny) etc. On the other hand this is the first psychological analysis of this problemin Albanian, targeting all social classes making it more understandable to parents and families in such conditions. Theparticipants in this study were seven families who have children of age 7 â€“ 9 and one parent diagnosed with cancer. The familiesare patients at the Oncologic Hospital Mother Teresa, Tirana. Two of them have a member hospitalized as a result of chirurgicalintervention and the other five have patients who have regular visits to the hospital due to medical examinations orchemotherapy. Three methods were used to measure the inferiority complex. They are: â€œRosenbergâ€™s self-evaluationâ€, â€œPRQâ€and a semi structured interview for identifying the parent-child relationship and the perfectionist behaviors that compensate theinferiority complex. This study shows that children, knowing the situation the family is in and wanting to get attention, act withperfectionist ideas and try to relieve burden from their parents. However, the more they go on with these behaviors the morethey feel left out and reach a point of very low self-esteem. In this article it is shown how one event leads to another and a verystrong and obvious base is formed for the formation of the inferiority complex. The article also advises families to prevent thiscondition by consulting with a psychologist.